A Family Report of Hereditary Gingival Fibromatosis - Mohammed Taib Fatih; Renaz Sabir Saleh; Mohammed Khalid Mahmood; Zana Fuad Noori; Handren Ameer Kurda; Mohammed Aso Abdulghafor (Hindawi Limited, 2024)
Conclusion: Proliferative fibrous outgrowth of the gingival tissue, with different degrees of involvement, is a hallmark of HGF. Surgery is frequently necessary to restore function and appearance, though varying degrees of recurrence is anticipated. Nonetheless, the psychological advantages of cosmetic improvement exceed the dangers of recurrence by a wide margin, especially in teenagers.